Delays in international criminal justice: What impact does it have on victims' rights? - Ovide Manzanga Kpanya (Ius Poenale, 2023)
This study aims to argue that the time of the criminal response at the international level is one neglected factor with unpredictable and sometimes irreversible consequences on the rights of victims. Speaking of delays, the idea is to demonstrate that this justice system does not react or act within a time limit that would prevent the deterioration of a situation, already disastrous and unbearable, in which the victims of these crimes. The resulting conclusions reveal that the set of rights enjoyed by these victims, until now, are not sufficient to protect them against these delays. And yet, the suffering they endure from the commission of these crimes justifies a substantial strengthening of their rights in order to avoid additional tortures, arising over time as long as justice has not resolved these conflicts, and will not have restored them to their violated rights.